Outcomes of midfoot and hindfoot fractures in multitrauma patients. Issue 2 (February 2019) - Diacon, A.L.; Kimmel, L.A.; Hau, R.C.; Gabbe, B.J.; Edwards, E.R.
Highlights: A regional comparison between hindfoot and midfoot fractures to further delineate outcomes has not been performed. Midfoot fractures may result in similar outcomes to hindfoot fractures in the multitrauma population. Supplements the literature that foot fractures are pronounced contributors to patient morbidity in the multitrauma setting. Midfoot and hindfoot fractures should be assessed and managed with a high degree of due diligence in the multitrauma patient. Abstract: Introduction: Multitrauma patients suffering hindfoot fractures, including calcaneal and talar fractures, often result in poor outcomes. However, less is known about the outcomes following midfoot fracture in the mutitrauma population. This study aims to describe the epidemiology of midfoot fractures in multitrauma patients and to compare the outcomes of midfoot and hindfoot fractures in this population. Methods: Data about multitrauma patients (Injury Severity Score >12) sustaining a unilateral midfoot or hindfoot fracture were obtained from the Victorian Orthopaedic Trauma Outcomes Registry (VOTOR) and from retrospective review of medical records at a major trauma centre. Further outcome data were obtained via a survey using the American Academy of Orthopedic Surgeons Foot and Ankle Score (AAOS FAS) and the 12-item Short Form Health Survey (SF-12). Results: 122 multitrauma patients were included; 81 with hindfoot fractures and 41 with midfoot fractures. The median ISS (IQR) was 22 (17–29) and 27 (17–24) for the hindfoot and midfoot groups, respectively (p = 0.23). Hindfoot and midfoot fractures were commonly associated with intracranial injuries (80.3%), spine injuries (60.7%), ipsilateral lower extremity injuries (24.6%) and pelvic injuries (16.4%). The mean (SD) time to follow up was 4.5 (±2.7) years. There were no differences in mean SF-12 physical (37.97 vs 35.22, p = 0.33) or mental (46.90 vs 46.67, p = 0.94) component summary scores between the groups. There were no differences in mean AAOS FAS standard scores (69.3 vs 69.1, p = 0.97) or shoe comfort scores (median 40 vs 40 p = 0.18) between the groups. Conclusion: Functional outcomes in multitrauma patients with midfoot or hindfoot fractures were comparable. These findings suggest that midfoot fractures should be treated with the same degree of due diligence as hindfoot fractures in the multitrauma patient.